Do-It-Yourself Insect Pest Traps - Steven Arthurs; Adrian Hunsberger (EDIS)
Many types of traps can be used to monitor or control insect pests. Traps to capture insects vary greatly, depending on the target, location, and purpose. Traps may be inexpensive and disposable, or more complex. This 12-page fact sheet describes several traps for common pests in the home, garden, and landscape that can be made using common household materials or that are readily available in stores. Written by Steven Arthurs and Adrian Hunsberger, and published by the Entomology and Nematology Department, December 2015.